A HANGING IN SHADOWS: THE AFZAL GURU CONTROVERSY - Priyal Mehta, (The American Journal of Political Science Law and Criminology, 2024)
The execution of Afzal Guru, convicted for his involvement in the 2001 Indian Parliament attack, remains one of the most controversial and debated events in contemporary Indian history. This study delves into the multifaceted dimensions of Guru's trial, conviction, and eventual hanging, examining the legal, political, and societal implications surrounding the case. Through a critical analysis of court documents, media narratives, and public opinion, the study explores the questions of judicial fairness, political motivations, and the impact on India's democratic and legal institutions. By uncovering the complexities and contradictions of the case, this paper aims to provide a nuanced understanding of how justice, politics, and public perception intersected in the Afzal Guru controversy, raising broader questions about the rule of law and human rights in India.